1998
DOI: 10.1210/endo.139.11.6283
|View full text |Cite
|
Sign up to set email alerts
|

The Thyrotropin β-Subunit Gene Is Repressed by Thyroid Hormone in a Novel Thyrotrope Cell Line, Mouse TαT1 Cells**This work was supported by NIH Research Grants R01-HD-20377 and HD-12303 (to P.L.M.) and R01-DK-36843 (to E.C.R.); fellowships from the Spanish Ministry of Education and Science and Fundacion Jaime del Amo, Universidad Complutense de Madrid, Spain (to B.Y.); and a Ford Foundation Fellowship, the President’s Fellowship of the University of California, and NIH National Research Scientist Award Fe

Abstract: TSH is expressed in two populations of thyrotropes in the pituitary: one in the pars distalis and a second in the pars tuberalis. Pars distalis thyrotropes exhibit classical endocrine inhibition of TSH by thyroid hormone, whereas pars tuberalis thyrotropes do not. The majority of our understanding of TSH subunit gene regulation has come from studies conducted in dispersed pituitary, dispersed thyrotropic tumors, or the GH 3 somatolactotrope cell line. However, the dispersed pituitary model is limited because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Next, we examined the inhibitory effect of liganded TRβ2 in the cells, where the GATA2 gene is endogenously expressed presumably via its positive feedback loop. While TαT1 is known to be a thyrotroph cell line [48], its GATA2 protein expression level is modest [8]; we found that the suppressive effect of T3 on TSHβ and the CGA mRNA was mild (data not shown) and completely lost, respectively. Other candidates are gonadotroph-derived LβT2 [43] and choriocarcinoma-derived JEG3 [52], both of which express the CGA gene [30, 34,35,52].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Next, we examined the inhibitory effect of liganded TRβ2 in the cells, where the GATA2 gene is endogenously expressed presumably via its positive feedback loop. While TαT1 is known to be a thyrotroph cell line [48], its GATA2 protein expression level is modest [8]; we found that the suppressive effect of T3 on TSHβ and the CGA mRNA was mild (data not shown) and completely lost, respectively. Other candidates are gonadotroph-derived LβT2 [43] and choriocarcinoma-derived JEG3 [52], both of which express the CGA gene [30, 34,35,52].…”
Section: Resultsmentioning
confidence: 60%
“…Cells were harvested after incubation for an additional 24 hr, and CAT activity was measured as described previously [17]. Mouse thyrotroph-derived TαT1 cells [48] (a kind gift from Dr. Pamela Mellon, University of California, CA, USA) were seeded on Matrigel-coated plates (Becton Dickinson Labware, Bedford, MA, USA). LβT2 cells, a mouse gonadotroph cell line [43], were cultured in DMEM supplemented with 10% FCS.…”
Section: Cell Culture and Transient Transfectionmentioning
confidence: 99%
“…However, it has since been learned that Pit-1 is probably minimally involved, and that GATA-2 may be the primary activator of TRH-driven transcription of the TSHβ gene (4346). Other studies have shown that thyroid hormone negatively regulates TSHβ by interfering with the binding of transcription factors near the proximal promoter region (47, 48). In the case of immune system TSHβv, no transcription factors have, as yet, been linked to gene activation.…”
Section: The Tshβ Splice Variant (Tshβv)mentioning
confidence: 99%
“…These actions are rapidly triggered even in the presence of transcription inhibitors (Yusta et al 1998, Lorenzo et al 2002 by TH interactions with THRs coupled to specific enzymes in the cytosol or to other binding sites located on the plasma membrane and organelles such as mitochondria and endoplasmic reticulum (Moeller et al 2006, Davis et al 2008, 2009, Goulart-Silva et al 2011.…”
Section: Non-genomic Actions Of Thsmentioning
confidence: 99%